2013
DOI: 10.1097/qai.0b013e3182a9213a
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection Is Associated With Diffusing Capacity Impairment in Women

Abstract: Respiratory dysfunction is common in HIV, but few studies have directly assessed whether HIV remains an independent risk factor for pulmonary function abnormalities in the antiretroviral therapy era. Additionally, few studies have focused on pulmonary outcomes in HIV+ women. We tested associations between risk factors for respiratory dysfunction and pulmonary outcomes in 63 HIV+ and 36 HIV-uninfected women enrolled in the Women’s Interagency HIV Study. Diffusing capacity (DLCO) was significantly lower in HIV+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 36 publications
(45 reference statements)
5
69
2
Order By: Relevance
“…As people were not randomly selected to participate, recruitment bias is possible. Spirometry was our only objective measure of lung function, whereas several studies have suggested that impairment of gas transfer is more common than airflow obstruction in PLWH [28,29]. The differences in age and ethnicity between groups could have influenced our results; however, our findings persisted after adjustment in multivariable analyses; and our sensitivity analysis is reassuring in that the difference in age distribution between HIV-positive and HIV-negative participants appeared to have little impact on the results.…”
Section: Discussioncontrasting
confidence: 52%
“…As people were not randomly selected to participate, recruitment bias is possible. Spirometry was our only objective measure of lung function, whereas several studies have suggested that impairment of gas transfer is more common than airflow obstruction in PLWH [28,29]. The differences in age and ethnicity between groups could have influenced our results; however, our findings persisted after adjustment in multivariable analyses; and our sensitivity analysis is reassuring in that the difference in age distribution between HIV-positive and HIV-negative participants appeared to have little impact on the results.…”
Section: Discussioncontrasting
confidence: 52%
“…11,47,52,53 DLCO of less than 80% predicted was present in 64% of HIV-infected patients from one study, 11 and was independently associated with greater numbers of pack-years smoked, and use of pneumocystis prophylaxis (an indicator of lower CD4 cell counts), but not ART use. 11 In an analysis of 300 HIV-infected men and 289 HIV-uninfected men from the Lung-HIV cohort, 54 a moderate to severe reduction in DLCO was noted in 30% of HIV-infected patients compared with 18% of HIV-uninfected people (p<0·001).…”
Section: Abnormalities In Pulmonary Function Tests In Patients With Hivmentioning
confidence: 94%
“…Chronic lung diseases, such as COPD, have long been postulated to have an infectious component. COPD is an important cause of respiratory impairment in HIV-infected persons, and HIV infection is an independent risk factor for COPD (6,13,40). Pulmonary infections could stimulate replication of HIV in the lungs, augment pulmonary inflammation, and cause lung destruction by release of proteases, thereby leading to or worsening COPD (41).…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-six participants were recruited at the University of Pittsburgh, the University of California San Francisco, and the University of California Los Angeles (6,13). Subjects were outpatients not experiencing an acute change in respiratory symptoms in the prior 4 weeks and had not received antibiotics in the previous 6 months.…”
Section: Methods Study Participantsmentioning
confidence: 99%